2013
DOI: 10.4102/phcfm.v5i1.477
|View full text |Cite
|
Sign up to set email alerts
|

Community oriented primary care in Tshwane District, South Africa: Assessing the first phase of implementation

Abstract: BackgroundRe-engineering primary health care is a cornerstone of the health sector reform initiated nationally in South Africa in 2009. Using the concept of ward based NGO-run health posts, Tshwane District, Gauteng, began implementing community oriented primary care (COPC) through ward based outreach teams (WBOT) in seven wards during 2011.ObjectivesThis study sought to gain insight into how primary health care providers understood and perceived the first phase of implementing COPC in the Tshwane district.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 24 publications
0
41
0
Order By: Relevance
“…A proposed solution to South Africa's access to health care difficulties relating to prevention has been to move towards community-based primary care in an attempt re-engineer the primary health care system (Kinkel, Marcus, Memon, Bam, & Hugo, 2012). A policy paper released by the National Department of Health (2011) called for a renewed emphasis on health promotion and prevention care and also indicated that services should include community health care workers (CHWs) involved in community outreach and homebased services.…”
Section: Introductionmentioning
confidence: 99%
“…A proposed solution to South Africa's access to health care difficulties relating to prevention has been to move towards community-based primary care in an attempt re-engineer the primary health care system (Kinkel, Marcus, Memon, Bam, & Hugo, 2012). A policy paper released by the National Department of Health (2011) called for a renewed emphasis on health promotion and prevention care and also indicated that services should include community health care workers (CHWs) involved in community outreach and homebased services.…”
Section: Introductionmentioning
confidence: 99%
“…This approach enables the team to work from a sound understanding of the local culture and idiom, although there is the risk of overfamiliarity and problems associated with privacy. 25 For the most part, the health post is hosted by existing community-based nonprofit organisations (NPOs). This approach to COPC was deliberately adopted because these organisations have historically established structures and links in the communities.…”
Section: What the Health Post Ismentioning
confidence: 99%
“…[7,8] Local, private general practitioners (GPs) are excited about supporting WBOTs and in the next phase GPs will work directly with these teams. In this way, the GP will be able to provide COPC to families in his/her community.…”
Section: Models Of Generalism For the South African Contextmentioning
confidence: 99%